Manufacturing method of slide member, slide member, and piston ring

JP7634799B1Active Publication Date: 2025-02-21RIKEN CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024562838
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-21
Estimated Expiration
2044-09-30

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、過酷な環境下であっても耐剥離性に優れると共に、耐摩耗性及び相手攻撃性のバランスがよく、且つ、十分に高水準に達成できる摺動部材の製造方法、摺動部材、及びピストンリングが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634799000002
    Figure 0007634799000002
  • Figure 0007634799000003
    Figure 0007634799000003
  • Figure 0007634799000004
    Figure 0007634799000004
Patent Text Reader

Abstract

A method for producing a slide member comprising a substrate and a coating provided so as to cover at least a portion of the surface of the substrate, the method comprising: (A) a step of obtaining an intermetallic compound containing Cr and a metal element including at least Si; and (B) a step of forming a coating using the intermetallic compound by an arc ion plating method, wherein in the step (B), a bias voltage is set in the range of -2 to -25 V under a nitrogen atmosphere. A slide member comprising a substrate and a coating provided so as to cover at least a portion of the surface of the substrate, the coating containing Cr, N, and a metal element including at least Si, the coating having a base portion and a dispersed particle portion scattered within the base portion, and a hardness of the coating being 1900 HV0.1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a manufacturing method of a slide member, a slide member, and a piston ring. [Background technology]

[0002] Sliding members such as piston rings are used in engines of automobiles and the like. Piston rings are fitted in grooves provided on the outer peripheral surface of pistons. Piston rings are required to contribute to high performance of engines and reduced fuel consumption by, for example, their wear resistance and seizure resistance. Conventionally, various efforts have been made to improve the wear resistance of piston rings.

[0003] For example, the invention described in Patent Document 1 was made to provide a sliding member that has excellent wear resistance even under the severe conditions in an engine to which direct fuel injection or exhaust gas recirculation (EGR) is applied. This sliding member has a substrate coated with a coating having a mixed structure of a crystalline phase and an amorphous phase, the crystalline phase being made of a metal nitride, a metal carbide, or a metal carbonitride.

[0004] The invention described in Patent Document 2 was made to provide a piston ring for an internal combustion engine that combines wear resistance with crack resistance and peeling resistance. This piston ring has a hard coating formed at least on the outer peripheral sliding surface, the hard coating being composed of a crystal phase that contains Cr, N and Si as constituent elements, has the same crystal structure as CrN, and has Si in a solid solution at a ratio of 1% or more and 9.5% or less in the crystal lattice. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2002-266697 A [Patent Document 2] JP 2008-14228 A Summary of the Invention [Problem to be solved by the invention]

[0006] Sliding members are required to have not only excellent wear resistance but also low aggression toward mating materials. Therefore, a high level of balance is required so that neither the sliding member nor the mating material is worn. Furthermore, in recent years, in order to meet the needs of higher engine power and exhaust gas regulations, for example, higher combustion temperatures, adoption of low-viscosity lubricants, and reduction in the amount of oil have progressed. In addition, FFVs (Flex Fuel Vehicles) that are adjusted to a wide range of mixture ratios of gasoline and biofuel are being distributed. As a result, the operating environment of sliding members has become harsher and more boundary lubricated, and not only the amount of wear of the film on the sliding members has increased, but also peeling of the film due to increased sliding resistance has become an issue.

[0007] Therefore, the present invention provides a manufacturing method for a slide member, a slide member, and a piston ring which have excellent peeling resistance even in severe environments, a good balance between wear resistance and attacking properties on mating members, and which can achieve a sufficiently high level of properties. [Means for solving the problem]

[0008] The present invention includes, for example, the following. [1] A method for producing a slide member comprising a substrate and a coating provided so as to cover at least a portion of a surface of the substrate, the method comprising the steps of: (A) obtaining an intermetallic compound containing Cr and a metal element including at least Si; (B) forming the coating by an arc ion plating method using the intermetallic compound; Including, A manufacturing method in which a bias voltage in the range of −2 to −25 V is set in a nitrogen atmosphere in the step (B). [2] A substrate; A coating provided so as to cover at least a portion of a surface of the substrate; Equipped with The coating contains Cr and N and a metal element including at least Si, The coating has a base portion and a dispersed particle portion scattered within the base portion, A sliding member, wherein the hardness of the coating is 1900HV0.1 or less. [3] The sliding member according to [2], wherein the metal element includes at least one selected from the group consisting of Ti, Al, Mo, V, W, Nb, Mn, Zn, Cu, and Zr. [4] The slide member according to [2] or [3], wherein the content of the metal element in the base portion is 1 to 25 at %. [5] The sliding member according to any one of [2] to [4], wherein the content of the metal element in the dispersed particle portion is greater than the content of the metal element in the base portion. [6] The sliding member according to any one of [2] to [5], wherein the coating has a hardness of 800 HV0.1 to 1500 HV0.1. [7] A piston ring comprising the sliding member according to any one of [2] to [6]. Effect of the Invention

[0009] According to the present invention, there are provided a manufacturing method for a slide member, a slide member, and a piston ring which have excellent peel resistance even in severe environments, a good balance between wear resistance and attack resistance against mating members, and which can achieve a sufficiently high level of properties. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a sliding member according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of the surface of a coating in a sliding member according to one embodiment of the present invention. [Diagram 3] FIG. 3 shows the results of EPMA analysis of the surface of the piston ring of Example 1. [Figure 4] FIG. 4 is a binarized image of the surface of the piston ring of Example 1. [Diagram 5] FIG. 5 is a schematic diagram showing the configuration of a sliding fatigue testing machine. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the following embodiment.

[0012] (Sliding member) FIG. 1 is a schematic cross-sectional view of a slide member according to one embodiment of the present invention. The slide member 10 shown in FIG. 1 includes a substrate 1 and a coating 5 provided so as to cover at least a part of the surface of the substrate 1. The coating 5 may be provided on the outer circumferential surface of the substrate 1 (the surface corresponding to the sliding surface 10F). The slide member 10 is, for example, a compression ring (piston ring) for an internal combustion engine (for example, an automobile engine). The compression ring is mounted in, for example, a ring groove formed on the side surface of a piston. The compression ring is a ring that is particularly exposed to an environment of high thermal load in the engine.

[0013] When the sliding member is a piston ring, the piston ring is annular and has an outer diameter of, for example, 40 to 300 mm. The "annular" here may be a closed circle or a substantially circular shape having an opening. The piston ring may be a perfect circle or an ellipse in plan view. The piston ring may be substantially rectangular in cross section, and the sliding surface may be rounded and bulged outward.

[0014] The substrate is made of a heat-resistant alloy, specific examples of which include spring steel and martensitic stainless steel, and the substrate may have a nitride layer formed on its surface.

[0015] The coating is made of a Cr-Me-N material (Me represents a metal element). The metal element Me contains at least Si from the viewpoint of achieving a better balance of wear resistance, peel resistance, and attacking properties. In addition to Si, the metal element Me may further contain at least one element selected from the group consisting of Ti, Al, Mo, V, W, Nb, Mn, Zn, Cu, and Zr.

[0016] The thickness of the coating may be, for example, 5 to 70 μm, or 10 to 50 μm. A coating thickness of 5 μm or more tends to increase the durability of the sliding member, while a thickness of 70 μm or less ensures high productivity of the coating.

[0017] 2, the coating 5 has a base portion 5A and a dispersed particle portion 5B scattered within the base portion 5A. The fact that the coating has a base portion and a dispersed particle portion can be confirmed from a backscattered electron image obtained by observing the coating with a scanning electron microscope (SEM or FE-SEM).

[0018] The base portion and the dispersed particle portion are each made of a Cr-Me-N-based material, but the content of each element is different. The content of the metal element in the dispersed particle portion may be greater than the content of the metal element in the base portion, from the viewpoint of a better balance of wear resistance, peel resistance, and attacking properties. The dispersed particle portion containing a metal element such as Si is also called an alloy dispersed particle portion.

[0019] The equivalent circle diameter of the dispersed particle portion is, for example, 0.1 to 10 μm. The equivalent circle diameter of the dispersed particle portion can be measured based on a backscattered electron image obtained by observing the surface of the coating with an SEM or the like.

[0020] The elemental composition of the base portion and the dispersed particle portion of the sliding member is measured by the following method. That is, first, the surface of the coating formed on the outer peripheral surface of the sliding member is polished with a polishing machine (e.g., IS-POLISHER manufactured by Ikegami Seiki Co., Ltd.). Specifically, the grit size is gradually increased from #600, and finally, a sample is obtained by polishing with a diamond film with a grit size of 0.5 μm. Next, an element concentration map is obtained from the obtained sample using an EPMA (e.g., JXA-8100 manufactured by JEOL Ltd.). The measurement conditions are an acceleration voltage of 15 kV and an irradiation current of 5.0×10 -8A, beam diameter 0μm (minimum setting), scan interval (vertical: 0.30μm, horizontal: 0.30μm), scan time 30ms / point, number of scan points (vertical: 200 points x horizontal: 200 points), and concentration map (60μm x 60μm) of each analyzed element are obtained. Note that even if the measurement beam diameter is set to the minimum setting value of the EPMA, the actual beam diameter will not be 0μm, but will be on the order of nm. Regarding the element amount in the base part and the dispersed particle part, the largest dispersed particle part (dispersed particle part with at least a circle equivalent diameter of 2μm or more) is selected in the concentration map, and a line scan is performed to pass through that dispersed particle part, and the concentration of each element for the scan position is obtained in the profile. When a small dispersed particle is scanned, the base part around the dispersed particle is also analyzed, so the element concentration in the dispersed particle part is not the true value, but is shifted to the element concentration side of the base part, which is not preferable. In the concentration profile of the line scan obtained in this manner, the baseline of the profile is taken as the average concentration of the base portion, and the concentration of the portion corresponding to the dispersed particle portion is taken as the maximum concentration of the dispersed particles, and the concentration of the base portion and the concentration of the dispersed particle portion can be compared.

[0021] A sliding member according to one embodiment of the present invention has a coating containing Cr, N, and metal elements including at least Si, a base portion, and a dispersed particle portion scattered within the base portion, and the coating has a hardness of 1900HV0.1 or less, thereby exhibiting an excellent balance of wear resistance, peel resistance, and resistance to attacking a mating member. The inventors speculate that the reason for this is as follows. <1> The dispersed particles scattered within the base portion of the coating of the sliding member contain metal elements such as Si as well as Cr, so that the dispersed particle portion (alloy-containing dispersed particle portion) is firmly bonded to the base portion. This increases the toughness of the entire coating and makes it less likely to become a starting point for peeling due to sliding resistance, thereby improving peeling resistance. <2> By including not only Cr but also other metal elements in the dispersed particles, a lubricating coating called a tribofilm is formed by reaction with the lubricating oil when the coating slides against the mating material. The lubricating coating functions as a protective film, improving wear resistance and reducing attacking potential of the mating material. <3> If the hardness of the coating is too high, the coating will have low flexibility and stress will be easily concentrated, which will cause cracks to occur, the coating will be easily peeled off, and the mating material will be easily worn, but if the hardness of the coating is low to a certain extent, the peel resistance will be improved and the attacking tendency of the mating material can be reduced. In addition, generally, if the hardness of the coating is low, the wear resistance will tend to be insufficient, but if the dispersed particle portion contains a metal element such as Si, the wear resistance of the dispersed particle portion itself will be improved. Due to the above mechanism, the wear resistance of the entire coating can be ensured even if the hardness of the entire coating is small, and the toughness of the entire coating is increased, making the coating less likely to peel off and improving the peeling resistance, compared to a dispersed particle portion of simple Cr that does not contain metal elements such as Si. However, the mechanism of the present invention is not limited to the above.

[0022] From the viewpoint of achieving a better balance between wear resistance, peel resistance, and attacking properties, the Cr content in the base portion may be 30 at% or more, 35 at% or more, or 40 at% or more, and from the same viewpoint, it may be 60 at% or less, 55 at% or less, or 50 at% or less. From these viewpoints, the Cr content in the base portion may be 30 to 60 at%.

[0023] From the viewpoint of a better balance of wear resistance, peel resistance, and attacking property, the total content of the metal elements in the base portion may be 1 at% or more, 3 at% or more, or 5 at% or more, and from the same viewpoint, it may be 25 at% or less, 22 at% or less, 20 at% or less, 15 at% or less, 12 at% or less, 10 at% or less, 8 at% or less, 7 at% or less, 6 at% or less, 5 at% or less, 4 at% or less, 3.5 at% or less, or 3 at% or less. From these viewpoints, the total content of the metal elements in the base portion may be 1 to 25 at%, 1 to 20 at%, 1 to 12 at%, 1 to 8 at%, 1 to 5 at%, or 1 to 3 at%.

[0024] From the viewpoint of achieving a better balance between wear resistance, peel resistance, and attacking resistance, the Si content in the base portion may be 1 at% or more, 2 at% or more, or 3 at% or more, and from the same viewpoint, it may be 8 at% or less, 7 at% or less, 6 at% or less, 5 at% or less, 4 at% or less, 3.5 at% or less, or 3 at% or less. From these viewpoints, the Si content in the base portion may be 1 to 8 at%, 1 to 5 at%, or 1 to 3.5 at%.

[0025] From the viewpoint of achieving a better balance between wear resistance, peel resistance, and attacking resistance against a mating member, the Ti content in the base portion may be 0 at% or more, 4 at% or more, or 7 at% or more, and from the same viewpoint, it may be 25 at% or less, 20 at% or less, or 17 at% or less. From these viewpoints, the Ti content in the base portion may be 0 to 25 at%.

[0026] From the viewpoint of obtaining a better balance between wear resistance, peel resistance, and attacking properties, the total content of Si and Ti in the base portion may be 1 at% or more, 6 at% or more, or 10 at% or more, and from the same viewpoint, it may be 30 at% or less, 24 at% or less, or 20 at% or less. From these viewpoints, the total content of Si and Ti in the base portion may be 1 to 30 at%.

[0027] From the viewpoint of achieving a better balance between wear resistance, peel resistance, and attacking properties, the N content in the base portion may be 35 at% or more, 40 at% or more, or 45 at% or more, and from the same viewpoint, it may be 65 at% or less, 60 at% or less, or 55 at% or less. From these viewpoints, the N content in the base portion may be 35 to 65 at%.

[0028] The Cr content in the dispersed particle portion may be 40 at% or more, 45 at% or more, or 50 at% or more from the viewpoint of a better balance of wear resistance, peeling resistance, and attacking properties, and from the same viewpoint, may be 80 at% or less, 75 at% or less, or 70 at% or less. From these viewpoints, the Cr content in the dispersed particle portion may be 40 to 80 at%.

[0029] The total content of the metal elements in the dispersed particle portion may be 1 at% or more, 3 at% or more, or 5 at% or more from the viewpoint of a better balance of wear resistance, peel resistance, and attacking properties, and from the same viewpoint, may be 30 at% or less, 26 at% or less, 24 at% or less, 22 at% or less, 20 at% or less, 15 at% or less, or 10 at% or less. The total content of the metal elements in the dispersed particle portion may be 1 to 30 at%, 1 to 24 at%, 1 to 20 at%, 1 to 15 at%, or 1 to 10 at%.

[0030] From the viewpoint of obtaining a better balance between wear resistance, peel resistance, and aggressiveness against a mating member, the content of Si in the dispersed particle portion may be 2 at% or more, 3 at% or more, 4 at% or more, or 5 at% or more, and from the same viewpoint, it may be 15 at% or less, 13 at% or less, 10 at% or less, 8 at% or less, or 6 at% or less. From these viewpoints, the content of Si in the dispersed particle portion may be 2 to 15 at% or 3 to 10 at%.

[0031] The Ti content in the dispersed particle portion may be 0 at% or more, 6 at% or more, or 9 at% or more from the viewpoint of a better balance of wear resistance, peel resistance, and attacking properties, and from the same viewpoint, may be 30 at% or less, 22 at% or less, or 19 at% or less. From these viewpoints, the Ti content in the dispersed particle portion may be 0 to 30 at%.

[0032] The total content of Si and Ti in the dispersed particle portion may be 3 at% or more, 10 at% or more, or 14 at% or more from the viewpoint of a better balance of wear resistance, peel resistance, and attacking properties, and from the same viewpoint, may be 40 at% or less, 30 at% or less, or 25 at% or less. From these viewpoints, the total content of Si and Ti in the dispersed particle portion may be 3 to 40 at%.

[0033] The N content in the dispersed particle portion may be 10 at% or more, 15 at% or more, or 20 at% or more from the viewpoint of a better balance of wear resistance, peel resistance, and attacking properties, and from the same viewpoint, may be 50 at% or less, 45 at% or less, or 40 at% or less. From these viewpoints, the N content in the dispersed particle portion may be 10 to 50 at%.

[0034] The difference between the total content of metal elements in the dispersed particle portion and the total content of metal elements in the base portion (dispersed particle portion - base portion) may be 0.5 at% or more, 1 at% or more, or 1.5 at% or more, from the viewpoint of achieving a better balance of wear resistance, peel resistance, and attacking properties against the other party, and from the same viewpoint, may be 3 at% or less, 2.5 at% or less, or 2 at% or less.

[0035] The difference in the Si content between the dispersed particle portion and the base portion (dispersed particle portion - base portion) may be 1 at% or more, 2 at% or more, or 2.5 at% or more from the viewpoint of achieving a better balance of wear resistance, peel resistance, and attacking properties against the other member, and from the same viewpoint, may be 5 at% or less, 4 at% or less, or 3 at% or less.

[0036] The area ratio of the dispersed particle part having a circle equivalent diameter of 0.1 μm or more on the surface of the coating may be 0.5 to 5% from the viewpoint of a better balance of abrasion resistance, peeling resistance, and attacking ability of the mating member. When the area ratio of the dispersed particle part having a circle equivalent diameter of 0.1 μm or more is 0.5% or more, a suitable gap can be provided between the sliding member and the mating member, so that the balance of abrasion resistance, peeling resistance, and attacking ability of the mating member tends to be better. When the area ratio of the dispersed particle part having a circle equivalent diameter of 0.1 μm or more is 5% or less, the dropout of the dispersed particles can be suppressed, so that the balance of abrasion resistance, peeling resistance, and attacking ability of the mating member tends to be better. The area ratio of the dispersed particle part having a circle equivalent diameter of 0.1 μm or more on the surface of the coating may be more than 1.0%, or may be 4.5% or less, or 4% or less, from the viewpoint of a better balance of abrasion resistance, peeling resistance, and attacking ability of the mating member.

[0037] The area ratio of the dispersed particle part having a circle equivalent diameter of 0.1 μm or more on the surface of the film can be measured by the following method. That is, the surface of the film of the sliding member is polished using a polishing machine (for example, IS-POLISHER manufactured by Ikegami Seiki Co., Ltd.). Specifically, the grit size is gradually increased from #600, and finally polished with a diamond film having a grain size of 0.5 μm to obtain a sample. Next, the obtained sample is observed with an FE-SEM (for example, JSM-7100F manufactured by JEOL Ltd.), and a backscattered electron image is obtained at a magnification of 2000 times. A region of 45 μm × 62.5 μm is extracted from the obtained backscattered electron image, and the image is binarized using image analysis software (for example, A-image-kun manufactured by Asahi Kasei Engineering Co., Ltd.). The total area of ​​the dispersed particle part having a circle equivalent diameter of 0.1 μm or more is measured from the binarized image. The area ratio can be calculated by dividing the total area of ​​dispersed particles having an equivalent circle diameter of 0.1 μm or more by the measured area (45 μm×62.5 μm).

[0038] The hardness of the coating is 1900HV0.1 or less. By having the hardness of the coating be 1900HV0.1 or less, the balance between peel resistance and attack resistance against the mating member is excellent. The hardness of the coating may be 800 to 1800HV0.1, 800 to 1500HV0.1, 900 to 1500HV0.1, or 1000 to 1300HV0.1, from the viewpoint of being able to undergo moderate elastic deformation, reducing Hertz stress caused by sliding, and easily realizing excellent peel resistance. The hardness of the coating can be measured using a Vickers hardness tester (for example, device name: HM-220, manufactured by Mitutoyo) based on the method specified in ISO6507.

[0039] (Method of manufacturing slide member) Next, a method for producing the slide member will be described. The method for producing the slide member according to the present embodiment includes the following steps. (a) A step of obtaining an intermetallic compound containing Cr and a metal element including at least Si. (b) A process of forming a coating using an intermetallic compound by the arc ion plating method.

[0040] Step (a) is a step in which powder containing Cr and a metal element is mixed, cold molded, and sintered by hot isostatic pressing (HIP) or hot pressing to obtain an intermetallic compound of a predetermined shape.

[0041] In the step (a), first, a metal powder containing Cr and a metal powder containing Si are mixed in a predetermined amount, with Cr as the main constituent element and a metal element containing at least Si as the secondary constituent element. The metal powder may be a metal powder containing at least one selected from the group consisting of Ti, Al, Mo, V, W, Nb, Mn, Zn, Cu, and Zr in addition to the metal powder containing Cr and the metal powder containing Si. The metal powder may contain a plurality of metal elements. There is no particular limitation on the method for producing the metal powder. The metal powder may be a powder substantially composed of only a single element, or may be a powder obtained by melting and powdering a plurality of components. It may also be a powder obtained by alloying the solid phase, such as by mechanical alloying.

[0042] Next, the mixed metal powder is cold-formed into a predetermined shape using a press or the like, and sintered by hot isostatic pressing (HIP) or hot pressing to obtain a target material containing an intermetallic compound of a predetermined shape.

[0043] The temperature during sintering by hot isostatic pressing (HIP) or hot pressing may be, for example, 900 to 1300°C, or 900 to 1100°C.

[0044] The pressure when sintering by hot isostatic pressing (HIP) or hot pressing may be, for example, 100 to 140 MPa.

[0045] By adjusting the type, mixing ratio, and sintering conditions of the material components for obtaining the intermetallic compound, it is possible to adjust the amount of dispersed particles scattered during film formation and the size of the dispersed particle portion while dispersing the dispersed particles in the film. For example, by lowering the sintering pressure when obtaining the intermetallic compound, it is possible to suppress the generation of intermetallic compounds of metal elements such as Cr and Si in the dispersed particle portion in the film.

[0046] The method for producing a slide member may include a step of cleaning the surface of the substrate prior to step (b). For example, the method may include a step of performing a cleaning treatment by degreasing or shot blasting. In addition, the method for producing a slide member may include a step of performing bombardment cleaning in a chamber.

[0047] The formation of the coating in the step (b) can be carried out by an arc ion plating method. Specifically, a nitrogen atmosphere is created in the chamber, and a bias voltage is set in the range of -2 to -25 V. By setting the bias voltage to -2 to -25 V when forming the coating by the arc ion plating method using an intermetallic compound, the coating can be prevented from becoming too dense, and residual stress inside the coating can be alleviated. This makes it possible to manufacture a sliding member that has excellent peel resistance even under harsh environments, a good balance of wear resistance and attacking properties against mating members, and can achieve a sufficiently high level. The bias voltage may be -3 to -15 V, or -4 to -10 V, from the viewpoint of achieving a better balance of wear resistance, peel resistance, and attacking properties of the sliding member.

[0048] From the viewpoint of achieving a better balance between the wear resistance, peel resistance, and attacking property of the sliding member, the nitrogen pressure in the chamber may be 1 to 10 Pa, 2 to 8 Pa, or 4 to 6.5 Pa. The film formation temperature may be, for example, 300 to 500° C. The arc current may be 100 to 200 A.

[0049] The constituent elements ionized by the arc discharge from the target material containing the intermetallic compound are deposited on the substrate connected to the cathode, forming a base portion of a coating made of the constituent elements. At the same time, droplets generated at the arc spot on the surface of the intermetallic compound are also released and dispersed within the base portion as dispersed particle portions. EXAMPLES

[0050] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0051] (Invention Examples 1 to 14 and Comparative Examples 1 to 9) <Film formation> As the substrate of the sliding member (piston ring), JIS SWOSC-V (silicon-chromium steel oil tempered wire) was used and processed into a ring shape. Next, as a preparation for film formation, the substrate was degreased and cleaned, and then the ring substrate was placed in an ion plating device. Next, in the chamber, the chamber atmosphere was changed to nitrogen, and the target material (including a metal compound or an intermetallic compound) having the composition shown in Table 1 was ionized at the nitrogen pressure shown in Table 1, the bias voltage shown in Table 1, the film formation temperature of 400°C, and the film having a thickness of about 20 μm was formed on the substrate surface. At this time, the arc current was 150 A in invention examples 1 to 14 and comparative examples 1, 2, 4 to 6, 8, and 9, the arc current was 100 A in comparative example 3, and the arc current was 350 A in comparative example 7. The intermetallic compounds were prepared by mixing a metal powder containing Cr and a metal powder containing an optional metal element in a predetermined amount so as to obtain the target composition shown in Table 1, cold forming the mixture using a press, and then sintering the mixture by hot isostatic pressing (HIP) at a temperature in the range of 900 to 1300°C and a pressure in the range of 100 to 140 MPa.

[0052] The elemental composition of the base portion and the dispersed particle portion of the produced piston ring was measured by the following method. First, the surface of the film formed on the outer peripheral surface of the piston ring was polished with a polishing machine (IS-POLISHER manufactured by Ikegami Seiki Co., Ltd.). Specifically, the grit size was gradually increased from #600, and finally, a sample was obtained by polishing with a diamond film with a grit size of 0.5 μm. Next, an elemental concentration map was obtained from the obtained sample using an EPMA (device name: JXA-8100, manufactured by JEOL Ltd.). The measurement conditions were an acceleration voltage of 15 kV, an irradiation current of 5.0 × 10 -8A, beam diameter 0 μm (minimum setting value), scan interval (vertical direction: 0.30 μm, horizontal direction: 0.30 μm), scan time 30 ms / 1 point, number of scan points (vertical direction: 200 points × horizontal direction: 200 points), and concentration map (60 μm × 60 μm) of each analyzed element were obtained. For the element amount in the base part and the dispersed particle part, the largest dispersed particle part in the concentration map was selected, and a line scan was performed so as to pass through the dispersed particle part, and the concentration of each element with respect to the scan position was obtained by a profile. In the concentration profile of the line scan obtained in this way, the baseline of the profile was set as the average concentration of the base part, and the concentration of the part corresponding to the dispersed particle part was set as the maximum concentration of the dispersed particles, and the concentration of the base part and the concentration of the dispersed particle part were compared. The analysis result of the surface of the piston ring of Example 1 by EPMA is shown in FIG. 3. In FIG. 3, the darker the black part, the higher the concentration of Si.

[0053] [Table 1]

[0054] <Film characteristics> The properties of the coatings of the piston rings according to the examples and comparative examples are shown in Table 1. The properties were measured by the following methods. (Dispersed particle area ratio) The surface of the film of the piston ring produced was polished using a polishing machine (IS-POLISHER manufactured by Ikegami Seiki Co., Ltd.). Specifically, the grit size was gradually increased from #600, and finally polished with a diamond film with a grit size of 0.5 μm to obtain a sample. Next, the obtained sample was observed with an FE-SEM (JSM-7100F manufactured by JEOL Ltd.), and a backscattered electron image was obtained at a magnification of 2000 times. A region of 45 μm × 62.5 μm was extracted from the obtained backscattered electron image, and binarized using image analysis software (for example, A-zo-kun manufactured by Asahi Kasei Engineering Co., Ltd.). The binarized image of the surface of the piston ring of Example 1 is shown in FIG. 4. In FIG. 4, the black area is the base part, and the white area is the dispersed particle part. The total area of ​​the dispersed particle part having a circle equivalent diameter of 0.1 μm or more was measured from the binarized image. The area ratio of the dispersed particle portion was calculated by dividing the total area of ​​the dispersed particle portion having a circle equivalent diameter of 0.1 μm or more by the measured area (45 μm × 62.5 μm). The evaluation criteria for the dispersed particle portion area ratio are as follows. A: The area ratio is 1% or less. B: The area ratio is more than 1% and 4% or less. C: The area ratio is more than 4%.

[0055] (Hardness) The hardness HV of the coating was obtained by conducting a hardness test at a test load of 0.98 N using a Vickers hardness tester (device name: HM-220, manufactured by Mitutoyo) based on the method specified in ISO6507.

[0056] <Slip fatigue test> As an accelerated wear test, a sliding fatigue test was performed using a test machine configured as shown in Fig. 5. Test machine 50 shown in Fig. 5 includes a rotating drum 51, a mechanism for bringing test piece S (cut piece of piston ring) into contact with the surface of drum 51, a mechanism for repeatedly applying load to test piece S, and a mechanism for supplying lubricating oil to the sliding part. This allows the test piece to wear in a relatively short time. The test conditions were as follows: Test load: 20~80N, sine curve (50Hz) · Counterpart material (drum): SUJ2 heat-treated material (diameter 80 mm) - Operating speed: forward / reverse trapezoidal pattern operation Lubricant: Base oil (0.1cc drop once every 30 seconds) Drum surface temperature: 80℃ Test time: 5 cycles of 2 to 3 minutes each

[0057] <Evaluation> Table 1 shows the evaluation results of the films of the piston rings according to the examples and the comparative examples. For each evaluation result, 20 piston rings according to the examples and the comparative examples were produced and 20 sliding fatigue tests were carried out on these as evaluation subjects. The films after the sliding fatigue tests were visually observed to evaluate the peeling resistance of the films. In addition, the wear resistance and aggressiveness against the mating member were evaluated by taking the wear amount of the film of Comparative Example 1 as the wear amount of the conventional CrN film. The evaluation criteria were as follows. (peeling resistance) A: Of 20 samples, the occurrence rate of peeling is 40% or less. B: Of the 20 samples, the occurrence rate of peeling is more than 40% and less than 80%. C: Among 20 samples, the occurrence rate of peeling is 80% or more.

[0058] (Wear resistance) Wear amount when the wear amount of a conventional CrN coating is set at 1.0 A: The amount of wear is 0.7 or less. B: The amount of wear is more than 0.7 and less than 0.9. C: The amount of wear is 0.9 or more.

[0059] (Aggression of opponents) Wear amount when the wear amount of the mating material (heat-treated SUJ2 material) caused by a conventional CrN coating is taken as 1.0 A: The amount of wear is 1.0 or less. B: The amount of wear is more than 1.0 and less than 1.2. C: The amount of wear is 1.2 or more. [Industrial Applicability]

[0060] According to the present invention, there are provided a piston ring provided with a coating containing Cr, N, and at least one metallic element selected from the group consisting of Si, Ti, Al, Mo, V, and W, which is capable of achieving a well-balanced and sufficiently high level of wear resistance, peeling resistance, and attacking properties against mating members, and a method for producing the same. [Explanation of symbols]

[0061] 1...substrate, 5...coating, 5A...base portion, 5B...dispersed particle portion, 10...sliding member, 10F...sliding surface.

Claims

1. A method for producing a slide member including a substrate and a coating provided so as to cover at least a portion of a surface of the substrate, the method comprising the steps of: (A) obtaining an intermetallic compound containing Cr and a metal element including at least Si; (B) forming the coating by an arc ion plating method using the intermetallic compound; Including, In step (B), a bias voltage in the range of −2 to −25 V is set in a nitrogen atmosphere; The coating contains Cr and N and a metal element including at least Si, The coating has a base portion and a dispersed particle portion scattered within the base portion.

2. A substrate; A coating provided so as to cover at least a portion of a surface of the substrate; Equipped with The coating contains Cr and N and a metal element including at least Si, The coating has a base portion and a dispersed particle portion scattered within the base portion, the base portion contains Cr, N, and Si; The dispersed particle portion contains Cr, N, and Si, A sliding member, wherein the hardness of the coating is 1900 HV0.1 or less.

3. 3. The sliding member according to claim 2, wherein the metal element includes at least one selected from the group consisting of Ti, Al, Mo, V, W, Nb, Mn, Zn, Cu, and Zr.

4. 4. The slide member according to claim 2, wherein the content of said metal element in said base portion is 1 to 25 at %.

5. 4. The sliding member according to claim 2, wherein a content of the metal element in the dispersed particle portion is greater than a content of the metal element in the base portion.

6. 4. The sliding member according to claim 2, wherein the coating has a hardness of 800 to 1500 HV0.

1.

7. A piston ring comprising the sliding member according to claim 2 or 3.

Citation Information

Patent Citations

  • Combination of cylinder and piston ring

    JP2014129826A

  • Composite hard chromium plating film and sliding member coated with the same

    JP2014196533A

  • Piston ring for internal combustion engine

    JP2015102188A

  • covered sliding element

    JP2018513278A

  • Piston ring and manufacturing method thereof

    JP2022087131A